Cardiovascular disease manifestations in Chernobyl liquidators: 25 years later. Clinico-analytical review - I. L. Telkova (Кардиоваскулярная терапия и профилактика)
Aim. To analyse the results of clinical cardiovascular disease (CVD) monitoring and the specifics of CVD manifestations in Chernobyl liquidators, who were exposed to “low” radiation doses 25 years ago. Material and methods. In total, 402 Chernobyl liquidators were examined. One hundred eighty five individuals have been followed up for 15 years (1994-2009) and underwent primary and repeat cardiologic examination, such as coronary artery (CA) angiography, endomyocardial biopsy, computed spiral tomography of CA, peripheral artery ultrasound, and the assessment of hormone levels, carbohydrate metabolism, and cardiovascular function. Results. At the first stage of cardiovascular monitoring (1995-1999), the most prevalent forms of CVD among Chernobyl liquidators were arterial hypertension, AH (70,3%) and/or coronary microvascular coronary heart disease, MVCHD (58,9%). Ten-fifteen years later, the prevalence of AH had not changed substantially. The prevalence of atherosclerotic coronary heart disease (ACHD) had increased, partly due to CA atherosclerosis development in patients with earlier diagnosed MVCHD. Severity, manifestations, and outcomes of CVD in Chernobyl liquidators were dependent on a range of factors, such as age, duration and doses of radiation exposure, and subsequent lifestyle and work characteristics. Conclusion. Stabilisation of AH pathomorphosis and prevention of atherosclerotic progression of MVCHD were associated with early diagnostics of vascular pathology and effective CVD prevention.